Stochastic delamination processes – A comparative analysis. (1st April 2023) - Malkiel, N.; Rabinovitch, O.
Highlights: The stochastic evolution of delamination processes in layered structures is investigated. A spectrum of stochastic analysis methods are outlined, explored, and compared. The focus is put on the evolution of uncertainty with the evolution of the delamination. 2 axes of evolution are considered and implications of the choice of axis are thoroughly discussed. The consideration of uncertainty of the response as an evolving phenomenon gives new perspectives. Abstract: Delamination is a critical failure mode relevant to any form of a layered structure. The delamination is a highly nonlinear and unstable process that is subjected to an inevitable, high degree of uncertainty. However, in most of the available research, it is considered as a deterministic process and the consideration of the delamination as an evolving stochastic process is almost nonexistent. The current investigation studies the delamination failure as an evolving stochastic process, augments a spectrum of stochastic analysis methods for that purpose, and applies them to a sequence of delamination problems. The study demonstrates the relative merits and disadvantages of the different analysis methods, addresses new questions that arise when uncertainty is introduced into delamination problems and when the delamination is considered as an evolving process, examines the ability of the stochastic methods to answer these questions, and discusses their physical implications. By that, it offers a new point of view on the stochastic nature of delamination processes and suggests a structured methodology for its analysis.